Automated crater detection and counting using the hough transform - Galloway, M.; Benedix, G.; Bland, Phil; Paxman, J.; Towner, M.; Tan, T. (Institute of Electrical and Electronics Engineers Inc., 2014)
© 2014 IEEE. A manual process for detecting and counting craters on the surface of a planetary body becomes impractical when attempting to survey a large surface area. Similarly, existing automated methods that are effective for specific areas of focus are also impractical for a large data set. We report on the work completed so far in developing a crater detection system to automatically detect craters down to sub-km sizes, across a large portion of a planetary surface. Specifically, we assess the performance of a Hough Transform (HT) for the application and in particular the influence of its preprocessing edge detection phase. Tests are performed on high resolution images of the Martian surface, anticipating a large scale crater counting application for crater chronology on the surface of Mars.